GE_GERICHTE P/2307/2012 vom 11. Juli 2017 - GE Cour de justice (2017)
ESCROQUERIE ; ABUS D'AUTORITÉ ; PORNOGRAPHIE ; COAUTEUR(DROIT PÉNAL) ; PARTIE CIVILE ; TORT MORAL ; FIXATION DE LA PEINE | CP.146; CP.312; aCP.197; CPP.433; CPP.429; CPP.428